Evaluation of the coastal inundation and erosion process in the Mid-West coast of Western Australia - Perera, Withanage Sajantha Lakmali (Curtin University, 2016)
This study focused on the coastal inundation and erosion process in the Mid-West Coast of Western Australia. The process was evaluated for 1, 100 and 500 ARI events with future sea level rise using numerical modelling method. Statistical method was used to determine the extreme water level, wave and wind for selected ARI events. Overall modelling results clearly show that future climate change and sea level rise have adverse impacts on the selected coastal region.